Assessment of gamma radiation levels of beach sands in Bitlis region of Lake Van - Kuluozturk, Muhammed Fatih; Celik, Sule Karatepe; Dogru, Mahmut (Springer Heidelberg, 2020)
Natural gamma radioisotope activity concentration levels in beach sands in the Bitlis region of Lake Van, in eastern Turkey, were determined using an HPGe detector. A total of 15 different beach sand samples were collected from Ahlat, Adilcevaz, and Tatvan shoreline regions, and then(226)Ra,Th-232,K-40, and(137)Cs radioisotope activity concentrations were measured. Mean values of gamma emissions for each radioisotope were determined as 58.78, 65.89, 1590.25, and 4.84 Bq kg(-1)for(226)Ra,Th-232,K-40, and(137)Cs, respectively. Mean radium equivalent activity, absorbed gamma dose rate, annual effective dose, and external hazard index values were calculated as 275.45 Bq kg(-1), 135.41 nGy h(-1), 0.17 mSv year(-1), and 0.74, respectively.
4th International Conference on Computational and Experimental Science and Engineering (ICCESEN) -- OCT 04-08, 2017 -- Antalya, TURKEY
Keywords: Gamma emission; Beach sands; Lake Van